A biosurfactant-producing and iron-oxidizing mixotrophic bacterium as an environmentally friendly reagent for eco-green flotation of Indonesian complex Pb-Zn ores. (15th August 2021) - Sanwani, Edy; Chaerun, Siti Khodijah; Husni, Halimatul; Pamungkas, Trimoko; Rasyid, Muhammad Abdur
Graphical abstract: Highlights: Alicyclobacillus sp. can potentially be as an eco-friendly flotation reagent. Alicyclobacillus sp. as bioreagents exhibits high selectivity for Pb against Si. Bioflotation of complex Pb-Zn ores runs optimally at pH 3 with a 90.21% recovery. An optimum bioflotation parameter is at 60 min of conditioning time. An optimum bioflotation parameter is at 20% v/v bacterial cell concentrations. Abstract: In an effort to find new sources of reagents for flotation in mineral processing, local microorganisms originating from the surrounding mining areas and surrounding areas were tested to be alternative bioreagents. The bacterium Alicyclobacillus sp. (a new local bacterial strain) was chosen because of its easy growth and no biological risk, and its capability to oxidize iron and sulfur and produce biosurfactants. Batch experiments were conducted to study the effect of bacterial adaptation to minerals on bioflotation performances evaluated by the contact angle measurement of galena, sphalerite, and silica at various pHs. Furthermore, laboratory-scale experiments with the Denver flotation cells were conducted to investigate the effect of pH, bioreagent concentration and conditioning time on mineral grade and recovery. The results showed that the bacterium had a high recovery of Pb (90.21%) and Zn (80.83%) with grades of 4.82% and 8.91%, respectively. Although these results were lower than the collectors adopted by the industry (based on our flotation performance using conventional flotation reagents), the bacterium had the potential to be used in the future for mineral flotation as an alternative eco-friendly reagent, presenting as biodegradable, ecologically sustainable reagents.